Brosimine B and the biphasic dose-response: insights into hormesis and retinal neuroprotection - Fonseca, Susanne Suely Santos; S. Port’s, Natacha M.; Aguiar, Gisele Priscila Soares; Botelho, Eliã P.; Couto, Nádia M. G.; Pinheiro, Wandson Braamcamp Souza; Khayat, André Salim; Yamada, Elizabeth S.; Costa, Edmar T.; Sena, Chubert Bernardo C.; Arruda, Mara Silvia P.; Bahia, Carlomagno P.; et al. (Frontiers in Pharmacology, 2025)
IntroductionThe biphasic dose-response behavior, also known as hormesis, is a characteristic feature of numerous natural products. It is defined by beneficial effects at low concentrations and toxicity at higher doses. This study investigates the hormetic effects of Brosimine B, a flavonoid derived from Brosimum acutifolium, on retinal cell viability under oxidative stress.MethodsTo simulate ischemic conditions, we used an oxygen-glucose deprivation (OGD) model. Retinal cells were treated with varying concentrations of Brosimine B, and analyses of cell viability, reactive oxygen species (ROS) production, and antioxidant enzyme activity were performed.ResultsBrosimine B at 10 µM significantly enhanced cell viability and reduced ROS production, likely through modulation of oxidative stress-protective enzymes such as catalase. However, higher concentrations (>10 µM) induced cytotoxic effects. A computational modeling approach using a hormetic (inverted U-shaped) model revealed biologically interpretable parameters, including a peak response at 10.2 µM and a hormetic zone width (σ = 6.5 µM) (R2 = 0.984).DiscussionThese results confirm that Brosimine B exhibits hormetic neuroprotective effects within a well-defined concentration window, supporting its potential as a therapeutic agent for oxidative stress–related retinal damage. The study highlights the value of computational modeling in optimizing dose–response analyses, offering a framework for refining natural product therapies and predicting toxicological thresholds in pharmacological applications.